Make or break: the thermodynamic equilibrium of polyphosphate kinase-catalysed reactions - Keppler, Michael; Moser, Sandra; Jessen, Henning J.; Held, Christoph; Andexer, Jennifer N. (Beilstein Journal of Organic Chemistry, 2022)
Polyphosphate kinases (PPKs) have become popular biocatalysts for nucleotide 5'-triphosphate (NTP) synthesis and regeneration. Two unrelated families are described: PPK1 and PPK2. They are structurally unrelated and use different catalytic mechanisms. PPK1 enzymes prefer the usage of adenosine 5'-triphosphate (ATP) for polyphosphate (polyP) synthesis while PPK2 enzymes favour the reverse reaction. With the emerging use of PPK enzymes in biosynthesis, a deeper understanding of the enzymes and their thermodynamic reaction course is of need, especially in comparison to other kinases. Here, we tested four PPKs from different organisms under the same conditions without any coupling reactions. In comparison to other kinases using phosphate donors with comparably higher phosphate transfer potentials that are characterised by reaction yields close to full conversion, the PPK-catalysed reaction reaches an equilibrium in which about 30% ADP is left. These results were obtained for PPK1 and PPK2 enzymes, and are supported by theoretical data on the basic reaction. At high concentrations of substrate, the different kinetic preferences of PPK1 and PPK2 can be observed. The implications of these results for the application of PPKs in chemical synthesis and as enzymes for ATP regeneration systems are discussed.
Keywords: ATP regeneration; biocatalyst; ePC-SAFT; polyp; PPK

(untitled) - Kornberg, A.; Rao, N. N.; Ault-Riché, D. (Annu. Rev. Biochem., 1999)

(untitled) - Mailer, R. K. W.; Hänel, L.; Allende, M.; Renné, T. (Front. Med., 2019)

(untitled) - Rao, N. N.; Gómez-García, M. R.; Kornberg, A. (Annu. Rev. Biochem., 2009)

(untitled) - Kornberg, A.; Kornberg, S. R.; Simms, E. S. (Biochim. Biophys. Acta, 1956)

(untitled) - Ishige, K.; Zhang, H.; Kornberg, A. (Proc. Natl. Acad. Sci. U. S. A., 2002)

(untitled) - Motomura, K.; Hirota, R.; Okada, M.; Ikeda, T.; Ishida, T.; Kuroda, A. (Appl. Environ. Microbiol., 2014)

(untitled) - Mordhorst, S.; Singh, J.; Mohr, M. K. F.; Hinkelmann, R.; Keppler, M.; Jessen, H. J.; Andexer, J. N. (ChemBioChem, 2019)

(untitled) - Frank, C.; Teleki, A.; Jendrossek, D. (Appl. Microbiol. Biotechnol., 2020)

(untitled) - Sureka, K.; Dey, S.; Datta, P.; Singh, A. K.; Dasgupta, A.; Rodrigue, S.; Basu, J.; Kundu, M. (Mol. Microbiol., 2007)

(untitled) - Nocek, B.; Kochinyan, S.; Proudfoot, M.; Brown, G.; Evdokimova, E.; Osipiuk, J.; Edwards, A. M.; Savchenko, A.; Joachimiak, A.; Yakunin, A. F. (Proc. Natl. Acad. Sci. U. S. A., 2008)

(untitled) - Ahn, K.; Kornberg, A. (J. Biol. Chem., 1990)

(untitled) - Akiyama, M.; Crooke, E.; Kornberg, A. (J. Biol. Chem., 1992)

(untitled) - Zhu, Y.; Huang, W.; Lee, S. S. K.; Xu, W. (EMBO Rep., 2005)

(untitled) - Kumble, K. D.; Ahn, K.; Kornberg, A. (Proc. Natl. Acad. Sci. U. S. A., 1996)

(untitled) - Lindner, S. N.; Vidaurre, D.; Willbold, S.; Schoberth, S. M.; Wendisch, V. F. (Appl. Environ. Microbiol., 2007)

(untitled) - Parnell, A. E.; Mordhorst, S.; Kemper, F.; Giurrandino, M.; Prince, J. P.; Schwarzer, N. J.; Hofer, A.; Wohlwend, D.; Jessen, H. J.; Gerhardt, S.; Einsle, O.; Oyston, P. C. F.; et al. (Proc. Natl. Acad. Sci. U. S. A., 2018)

(untitled) - Nocek, B. P.; Khusnutdinova, A. N.; Ruszkowski, M.; Flick, R.; Burda, M.; Batyrova, K.; Brown, G.; Mucha, A.; Joachimiak, A.; Berlicki, Ł.; Yakunin, A. F. (ACS Catal., 2018)

(untitled) - Kamerlin, S. C. L.; Sharma, P. K.; Prasad, R. B.; Warshel, A. (Q. Rev. Biophys., 2013)

(untitled) - Zhang, H.; Ishige, K.; Kornberg, A. (Proc. Natl. Acad. Sci. U. S. A., 2002)

(untitled) - Ogawa, N.; Tzeng, C.-M.; Fraley, C. D.; Kornberg, A. (J. Bacteriol., 2000)

(untitled) - Kuroda, A.; Kornberg, A. (Proc. Natl. Acad. Sci. U. S. A., 1997)

(untitled) - Frisch, J.; Maršić, T.; Loderer, C. (Biomolecules, 2021)

(untitled) - Fehlau, M.; Kaspar, F.; Hellendahl, K. F.; Schollmeyer, J.; Neubauer, P.; Wagner, A. (Front. Bioeng. Biotechnol., 2020)

(untitled) - Andexer, J. N.; Richter, M. (ChemBioChem, 2015)

(untitled) - Abu, R.; Woodley, J. M. (ChemCatChem, 2015)

(untitled) - Langer, R. S.; Gardner, C. R.; Hamilton, B. K.; Colton, C. K. (AIChE J., 1977)

(untitled) - Dobson, G. P.; Hitchins, S.; Teague, W. E., Jr (J. Biol. Chem., 2002)

Lehninger Principles of Biochemistry - Nelson, D. L.; Cox, M. M.; Lehninger, A. L. (W.H. Freeman, 2017)

(untitled) - Greinert, T.; Vogel, K.; Maskow, T.; Held, C. (Sci. Rep., 2021)

(untitled) - Alberty, R. A. (Arch. Biochem. Biophys., 2006)

Free Energies of Hydrolysis and Decarboxylation - Lundblad, R. L.; Macdonald, F. (CRC Press, 2018)

Harper’s Illustrated Biochemistry - Rodwell, V. W.; Bender, D. A.; Botham, K. M.; Kennelly, P. J.; Weil, P. A. (McGraw Hill, 2018)

(untitled) - Meurer, F.; Do, H. T.; Sadowski, G.; Held, C. (Biophys. Chem., 2017)

(untitled) - Müller, W. E. G.; Schröder, H. C.; Wang, X. (Chem. Rev., 2019)

(untitled) - Vogel, K.; Greinert, T.; Harms, H.; Sadowski, G.; Held, C.; Maskow, T. (Biochim. Biophys. Acta, Gen. Subj., 2020)

(untitled) - Vogel, K.; Greinert, T.; Reichard, M.; Held, C.; Harms, H.; Maskow, T. (Int. J. Mol. Sci., 2020)

(untitled) - Wettermark, G.; Borglund, E.; Brolin, S. E. (Anal. Biochem., 1968)

(untitled) - Mordhorst, S.; Siegrist, J.; Müller, M.; Richter, M.; Andexer, J. N. (Angew. Chem., Int. Ed., 2017)

(untitled) - Popadić, D.; Mhaindarkar, D.; Dang Thai, M. H. N.; Hailes, H. C.; Mordhorst, S.; Andexer, J. N. (RSC Chem. Biol., 2021)

(untitled) - Schwander, T.; Schada von Borzyskowski, L.; Burgener, S.; Cortina, N. S.; Erb, T. J. (Science, 2016)

(untitled) - Schultheisz, H. L.; Szymczyna, B. R.; Scott, L. G.; Williamson, J. R. (ACS Chem. Biol., 2008)

(untitled) - Hennig, M.; Scott, L. G.; Sperling, E.; Bermel, W.; Williamson, J. R. (J. Am. Chem. Soc., 2007)

(untitled) - Da Costa, C. P.; Fedor, M. J.; Scott, L. G. (J. Am. Chem. Soc., 2007)

(untitled) - Sun, C.; Li, Z.; Ning, X.; Xu, W.; Li, Z. (Bioresour. Bioprocess., 2021)

(untitled) - Baughn, R. L.; Adalsteinsson, O.; Whitesides, G. M. (J. Am. Chem. Soc., 1978)

(untitled) - Nilsson, J.; Ståhl, S.; Lundeberg, J.; Uhlén, M.; Nygren, P.-Å. (Protein Expression Purif., 1997)

(untitled) - Terpe, K. (Appl. Microbiol. Biotechnol., 2003)

(untitled) - Zhu, Y.; Lee, S. S. K.; Xu, W. (Biochem. Biophys. Res. Commun., 2003)

(untitled) - Mordhorst, S.; Maurer, A.; Popadić, D.; Brech, J.; Andexer, J. N. (ChemCatChem, 2017)

(untitled) - Liu, S.; Li, Y.; Zhu, J. (Process Biochem. (Oxford, U. K.), 2016)

(untitled) - Ngivprom, U.; Lasin, P.; Khunnonkwao, P.; Worakaensai, S.; Jantama, K.; Kamkaew, A.; Lai, R.-Y. (ChemBioChem, 2022)

(untitled) - Held, C.; Sadowski, G. (Annu. Rev. Chem. Biomol. Eng., 2016)

(untitled) - Hoffmann, P.; Voges, M.; Held, C.; Sadowski, G. (Biophys. Chem., 2013)

(untitled) - Held, C.; Reschke, T.; Mohammad, S.; Luza, A.; Sadowski, G. (Chem. Eng. Res. Des., 2014)

(untitled) - Knierbein, M.; Wangler, A.; Luong, T. Q.; Winter, R.; Held, C.; Sadowski, G. (Phys. Chem. Chem. Phys., 2019)

(untitled) - Crans, D. C.; Kazlauskas, R. J.; Hirschbein, B. L.; Wong, C.-H.; Abril, O.; Whitesides, G. M. (Methods Enzymol., 1987)

(untitled) - Cao, H.; Li, C.; Zhao, J.; Wang, F.; Tan, T.; Liu, L. (Appl. Biochem. Biotechnol., 2018)

(untitled) - Resnick, S. M.; Zehnder, A. J. B. (Appl. Environ. Microbiol., 2000)

(untitled) - Zhang, X.; Wu, H.; Huang, B.; Li, Z.; Ye, Q. (J. Biotechnol., 2017)

(untitled) - Nahálka, J.; Pätoprstý, V. (Org. Biomol. Chem., 2009)